2011
DOI: 10.1105/tpc.111.089003
|View full text |Cite
|
Sign up to set email alerts
|

UV-C–Irradiated Arabidopsis and Tobacco Emit Volatiles That Trigger Genomic Instability in Neighboring Plants

Abstract: We have previously shown that local exposure of plants to stress results in a systemic increase in genome instability. Here, we show that UV-C–irradiated plants produce a volatile signal that triggers an increase in genome instability in neighboring nonirradiated Arabidopsis thaliana plants. This volatile signal is interspecific, as UV-C–irradiated Arabidopsis plants transmit genome destabilization to naive tobacco (Nicotiana tabacum) plants and vice versa. We report that plants exposed to the volatile hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 55 publications
1
40
1
Order By: Relevance
“…The data obtained mostly from the somatic homologous recombination (SHR) reporter lines suggests that repair of such damage seems to increase the frequency not only of meiotic but also SHR events (reviewed in Boyko and Kovalchuk, 2011;Waterworth et al, 2011). A number of research articles in this area suggest that increases in homologous recombination (HR) frequencies may be a programmed response to accelerate evolutionary adaption and generate new resistance traits, enabling greater genomic plasticity in plants in response to adverse environmental conditions (Molinier et al, 2006;Boyko and Kovalchuk, 2011;Yao et al, 2011). However, we question the validity of these conclusions since these data are obtained almost exclusively using the SHR reporter lines that are not adequately characterized in the published literature.…”
Section: Somatic Homologous Recombination Reporter Lines: Lack Of Sufmentioning
confidence: 99%
See 4 more Smart Citations
“…The data obtained mostly from the somatic homologous recombination (SHR) reporter lines suggests that repair of such damage seems to increase the frequency not only of meiotic but also SHR events (reviewed in Boyko and Kovalchuk, 2011;Waterworth et al, 2011). A number of research articles in this area suggest that increases in homologous recombination (HR) frequencies may be a programmed response to accelerate evolutionary adaption and generate new resistance traits, enabling greater genomic plasticity in plants in response to adverse environmental conditions (Molinier et al, 2006;Boyko and Kovalchuk, 2011;Yao et al, 2011). However, we question the validity of these conclusions since these data are obtained almost exclusively using the SHR reporter lines that are not adequately characterized in the published literature.…”
Section: Somatic Homologous Recombination Reporter Lines: Lack Of Sufmentioning
confidence: 99%
“…Stress (UV-C or flagellin) applied to Arabidopsis plants increased levels of HR that persisted in several subsequent, untreated generations (Molinier et al, 2006). Most recently, it was shown that volatile signals from stressed plants also trigger an increase in genome instability in neighboring unstressed plants (Yao et al, 2011).…”
Section: Somatic Homologous Recombination Reporter Lines: Lack Of Sufmentioning
confidence: 99%
See 3 more Smart Citations